ANALISIS PEMBIASAAN BUDAYA LITERASI UNTUK MEWUJUDKAN KEMAMPUAN BERPIKIR KRITIS DI SD MUHAMMADIYAH 4 BATU - Ajeng Rohmatun Arfiani; Arina Restian; Mariani Mariani (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2024)
Literacy is the ability to understand, identify, process, create written and printed material related to language skills. Literacy is integrated into all aspects of life, therefore it is necessary to instill a culture of literacy in students. Familiarization with literacy culture will increase students' insight and knowledge, thereby generating critical thinking skills. Critical thinking skills are very important in the 21st century, where the development of science and technology is very rapid. This research aims to analyze the habituation of literacy culture to realize critical thinking skills at SD Muhammadiyah 4 Batu. The research method uses descriptive qualitative research. Data collection techniques through interviews, observation, documentation of school principals, teachers and students. The results of the research show that SD Muhammadiyah 4 Batu has implemented literacy culture every day before lessons start and created a reading corner in each classroom, so that students have the habit of reading books, telling stories, discussing, and daring to give opinions in discussions. This shows that the habituation of literacy culture at Muhammadiyah 4 Batu Elementary School has given rise to critical thinking skills in students.